2021
DOI: 10.1111/vco.12771
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bladder cancer and lymphoma in dogs is associated with pollution indices by county of residence

Abstract: Human urothelial cell carcinoma (UCC) and non-Hodgkin lymphoma are considered environmental cancers in people, but less is known about environment risk for UCC and lymphoma in dogs. The objective of this study was to determine whether dogs with these cancers, compared to unaffected control dogs, live in counties with higher tap water contaminants or higher levels of air pollution as measured by the Environmental Protection Agency (EPA) and by National Air Toxics Assessment chemical exposure risk estimates. Dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
1
12
1
Order By: Relevance
“…Unlike previous studies in Boxer dogs, living in a county with elevated average ozone levels (over 70 ppm) was not associated with lymphoma risk in this population [ 40 ]. This was unexpected, as increased near-surface ozone levels generally indicate higher industrial pollutant burden.…”
Section: Discussioncontrasting
confidence: 73%
“…Unlike previous studies in Boxer dogs, living in a county with elevated average ozone levels (over 70 ppm) was not associated with lymphoma risk in this population [ 40 ]. This was unexpected, as increased near-surface ozone levels generally indicate higher industrial pollutant burden.…”
Section: Discussioncontrasting
confidence: 73%
“…We found that UCC dogs lived in areas with higher reported TTHM concentrations in municipal drinking water compared with unaffected dogs. This is consistent with our previous findings in a separate case–control population of dogs with UCC, 29 and along with our swimming pool data, supports the hypothesis that TTHM exposure may contribute to UCC risk in dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Total trihalomethanes (TTHMs) are chlorination byproducts found in drinking water, which have been associated with UCC in people 15 and in our recent study of a separate population of dogs with UCC. 29 Publicly available data on TTHM concentrations in municipal drinking water were accessed through the Environmental Working Group (https://www.ewg.org/tapwater/), which is a non-profit that compiles annual water monitoring data provided by public utilities. Water data were available from 2014 to 2019.…”
Section: Municipal Data On Chlorination Byproducts In Drinking Watermentioning
confidence: 99%
“…A more recent study found that dogs with bladder cancer lived in areas with higher ambient ozone levels compared to controls. 43 Although ozone is not a direct anthropogenic pollutant, it is influenced by solar radiation and the presence of airborne anthropogenic pollutants, such as volatile organic compounds, and is considered a marker for poor air quality. These data are consistent with human studies that have shown urban living environments and air pollution are associated with increased risk of bladder cancer incidence and mortality.…”
Section: Comparative Oncologymentioning
confidence: 99%